The influence of digital comic-assisted PBL Model on science learning motivation in grade V - Nuralifah Zakiyyah; Mayarni Mayarni (Himpunan Pengembang Kurikulum Indonesia, 2025)
Learning motivation has an important role in supporting the effectiveness of the learning process. However, the low motivation of students to learn in science lessons at the elementary school level is still a problem that needs more attention. It aims to see the influence of the Problem-Based Learning (PBL) model combined with digital comic media on the learning motivation of grade V elementary school students. This study applies a quantitative approach using a posttest-only control group design quasi-experimental design. The research sample was taken using probability sampling techniques and simple random sampling methods. The instrument, in the form of a learning motivation questionnaire, was tested for validity and distributed to two classes, namely the experimental class and the control class, consisting of 31 students in each class. Hypothesis testing using an Independent Samples T-test showed a significant difference between the two classes. The experimental class had a higher learning motivation than the control class. The results showed that students who participated in IPAS learning with the PBL model assisted by digital comics experienced a higher increase in learning motivation compared to students who participated in conventional learning. It can be concluded that the PBL model assisted by digital comics is effective in increasing the learning motivation of elementary school students in science subjects. Abstrak Motivasi belajar memiliki peranan penting dalam menunjang efektivitas proses pembelajaran. Namun, rendahnya motivasi belajar peserta didik pada pelajaran IPAS di tingkat sekolah dasar masih menjadi persoalan yang perlu mendapatkan perhatian lebih. Bertujuan untuk melihat pengaruh model Problem Based Learning (PBL) yang dikombinasikan dengan media komik digital terhadap motivasi belajar peserta didik kelas V sekolah dasar. Penelitian ini menerapkan pendekatan kuantitatif memakai desain quasi eksperimen tipe posttest-only control group design. Sampel penelitian diambil memakai teknik probability sampling dan metode simple random sampling. Instrumen yang dipakai berupa angket motivasi belajar teruji validitasnya dan dibagikan kepada dua kelas, yaitu kelas eksperimen dan kelas kontrol, terdiri dari 31 peserta didik tiap kelas. Uji hipotesis memakai Independent Samples T-test menyatakan adanya perbedaan signifikan antara kedua kelas. Kelas eksperimen mempunyai motivasi belajar yang lebih unggul dibanding kelas kontrol. Hasil penelitian menunjukkan bahwa peserta didik yang mengikuti pembelajaran IPAS dengan model PBL berbantuan komik digital mengalami peningkatan motivasi belajar yang lebih tinggi dibandingkan dengan peserta didik yang mengikuti pembelajaran konvensional. Dapat disimpulkan bahwa model PBL berbantuan komik digital efektif dalam meningkatkan motivasi belajar peserta didik sekolah dasar pada mata pelajaran IPAS. Kata Kunci: IPAS; komik digital; motivasi belajar